Sustainability Reporting Disclosure: Does Corporate Governance Internal Mechanism Matter? - Ilona, Desi (Lembaga Riset Penelitian dan PKM Aliansi Manajemen Indonesia, 2025)
This study determines the factors affecting the sustainability reporting disclosure from internal corporate governance mechanism. This mechanism is represented by three variables: board of commissioner size, audit committee size and concentrated ownership. This study uses the agency theory as underpinning theory. The final sample of this study is fifteen companies that disclose sustainability report. secondary data is employed, and the data is analyzed using multivariate regression analysis. the classical assumptions must be satisfied first before proceeding to regression. the result show that two hypotheses are rejected and one hypothesis is accepted. The accepted hypothesis implied that higher concentrated ownership improves the sustainability reporting disclosure.